2010
DOI: 10.1021/am100345g
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibers Doped with Dendritic Fluorophores for Protein Detection

Abstract: We report a solid-state, nanofiber-based optical sensor for detecting proteins with an anionic fluorescent dendrimer (AFD). The AFD was encapsulated in cellulose acetate (CA) electrospun nanofibers, which were deacetylated to cellulose to generate secondary porous structures that are desirable for enhancing molecular interactions, and thus better signaling. The protein sensing properties of the fibers were characterized by monitoring the fluorescence response of cytochrome c (cyt c), hemoglobin (Hgb), and bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…Either quenching or enhancement of the emission is found following the interaction with cytochrome c, hemoglobin, or bovine serum albumin. The observed behavior is explained by energy transfer, electron transfer, and repulsion forces between interacting compounds . The device is reusable, featuring a decrease of the overall fluorescence intensity by 15% over five sensing cycles.…”
Section: Optical Sensorsmentioning
confidence: 92%
“…Either quenching or enhancement of the emission is found following the interaction with cytochrome c, hemoglobin, or bovine serum albumin. The observed behavior is explained by energy transfer, electron transfer, and repulsion forces between interacting compounds . The device is reusable, featuring a decrease of the overall fluorescence intensity by 15% over five sensing cycles.…”
Section: Optical Sensorsmentioning
confidence: 92%
“…Other examples of optical sensors include nanofibers made by polyfluorene‐derivatives blended with PMMA, which display a high sensitivity toward plasmid DNA,56b and nanofibers made by a diphenylacetylene polymer, sensitive to explosive nitroaromatic compounds 120, 121. Optical sensors based on fluorescent nanofibers have also been developed for protein detection 122, 123. Wang et al124 have recently demonstrated ultrasensitive detection of explosives vapors, explosives residues on handprint and buried explosives, by means of emission quenching in a sensing film composed of electrospun nanofibers.…”
Section: Applications Of Active Nanofibersmentioning
confidence: 99%
“…11.6a, b). Davis et al [119] reported a protein sensor by encapsulating the anionic fluorescent dendrimer in electrospun CA fibers, which were deacetylated to cellulose to generate secondary porous structure that is desirable for enhancing molecular interactions. The results revealed that the sensor could be used to detect cytochrome-c of 0.1 M with good reversibility (Fig.…”
Section: Fluorescence Sensormentioning
confidence: 99%